Class Management in Improving Students' Reading Interest at Pondok Pesantren - Sari Kawuryan; Pardiman Pardiman; Djoni Harijanto (Nazhruna: Jurnal Pendidikan Islam, 2022)
This article describes the classroom management model in increasing interest in reading at Miftahul Huda Islamic Boarding School Lumajang. With their salaf characteristics, Islamic boarding schools continue to innovate continuously in classroom management to improve student literacy. This type of research is qualitative with a case study approach, data obtained from interviews, observations, and documentation, then analyzed by condensing, displaying data, and drawing conclusions. In this study, data analysis was carried out from the time of data collection as a whole and checked again to ensure the validity of the data. The findings of the study indicate that classroom management in improving literacy culture has an impact on increasing students' interest in reading at Miftahul Huda Islamic Boarding School Lumajang through 1) survey strategies, questions, reading, being read and reviewing reading results, 2) reading-questioning strategies, 3) Storytelling and read textbooks. Asatidz (teacher) is carrying out their function as a class manager by using management functions, namely class planning, class organization, classroom arrangement, and measurement of program achievement thorough evaluation.